A Bibliometric Study on the Impact of Social Tech Hubs on Social Innovation and Local Economic Development - Judijanto, Loso; Irwanto, Irwanto; Putri Mahadi, Nur Rizky (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of the scholarly literature on the impact of social tech hubs on social innovation and local economic development. Using data from the Scopus database and analytical tools such as VOSviewer, the study explores co-authorship networks, keyword co-occurrences, citation patterns, and thematic clusters. Results indicate that “social innovation” is the central concept in this domain, frequently associated with themes such as sustainable development, social entrepreneurship, and digital transformation. The field demonstrates a shift from earlier emphasis on open innovation and corporate responsibility to more recent interests in digital social innovation and sustainability goals. Leading contributors are concentrated in Europe, North America, and Australia, though there is growing representation from Asia, Latin America, and Africa. The findings highlight both the growing complexity and interdisciplinarity of the field, as well as its structural gaps—particularly in rural development, governance, and Global South collaboration. This study provides valuable insights for researchers, policymakers, and practitioners seeking to understand the evolving role of social tech hubs in advancing inclusive and sustainable innovation ecosystems.